Franchise Extension and Fiscal Structure in the United Kingdom 1820-1913: A New Test of the Redistribution Hypothesis - Toke Aidt; Stanley L. Winer; Peng Zhang (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study the effect of franchise extension on the fiscal structure of central and local governments in the United Kingdom between 1820 and 1913 to revisit the Redistribution Hypothesis - the prediction that franchise extension causes an increase in state-sponsored redistribution. We adopt a novel method of uncovering causality from non-experimental data proposed by Hoover (2001). This method is based on tests for structural breaks in the marginal and conditional distributions of the franchise and fiscal structure time series preceded by a detailed historical narrative analysis. We do not find any compelling evidence that supports the Redistribution Hypothesis.
Keywords: D72; 330; franchise extension; redistribution; democratization; causality; structural breaks; local government; central government; historical narrative